Handbook of research on emerging innovations in rail transportation engineering - Rai, B. Umesh 1959- (Advances in civil and industrial engineering (ACIE) Book series, 2016)
This book presents the latest research on next-generation public transportation infrastructures, emphasizing a diverse set of topics related to rail-based transportation such as funding issues, policy design, traffic planning and forecasting, and engineering solutions